Structural, optical and charge density investigations on lead free Mn2+ doped Cs2NaBiCl6 double perovskite microcrystals. (December 2022) - Jeevaraj, M.; Sudhahar, S.; Devendran, P.; Nallamuthu, N.; Jayram, Naidu Dhanpal; Kumar, M. Krishna
Abstract: Improved ambient stability and the non-toxicity of lead-free halide double perovskites have rendered them tremendous research focus in the recent years. However, their large indirect bandgap's limit their optoelectronic applications. Introduction of activator transition metal ion such as Mn 2+ in their lattices modifies their absorption and emission spectrum. In this article, we have successfully synthesized Mn 2+ doped Cs2 B′B′′Cl6 (B′= Na +, B′′=Bi 3+ ) microcrystals by chemical reflux method. Crystallinity and morphological analysis were studied using X-ray diffraction and scanning electron microscopy respectively. The elemental analysis was carried out using Energy dispersive X-ray (EDS) and X-ray photoelectron spectroscopy. A prominent emission at 585 nm in tune with the 4 T1 → 6 A1 transition of the Mn 2+ ions is observed from the photoluminescence studies and carrier recombination dynamics was analysed using time resolved photoluminescence spectroscopy. Electron density distribution studies were also carried out using Maximum entropy method to understand the nature of bonding in Mn 2+ :Cs2 NaBiCl6 double perovskites. Graphical Abstract: ga1 Highlights: Orange-red emission at 585 nm corresponding to Mn 2+ transitions. Energy transferred from Cs2 NaBiCl6 to dopant Mn 2+ ions. Mn 2+ doping preserves the cubic symmetry. Mn 2+ acts as both sensitizer and activator. Non-toxic, environment friendly, thermally stable, lead free double perovskite.